SYNTHESIS OF SOME 7-AZAINDOLE DERIVATIVES: THEIR CYTOTOXICITY AND ANTIBACTERIAL ACTIVITY - SAIFY, ZAFAR SAEED; HAIDER, SYED MOAZZAM; AHMED, MANSOOR; SAEED , MOHAMMAD; SIDDIQUI, BINA SHAHEEN; KHAN, ABDULLAH (Biological Sciences - PJSIR, 2022)
In thecourseofpharmaco-chemical studies, a number of new 7-azaindolederivatives have been prepared.The spectroscopic techniques such as IH NMR, ElMS, UV and IR were utilized for their structure elucidation. These compounds were tested against a variety of Gram + ve and Gram-ve bacteria. These compounds were also screened for their cytotoxicity against Artemia salina. Compound IV displayed significant antibacterial activity amongst all the tested compounds. Whereas compound VI was found to be the most significant cytotoxic when screened through brine shrimp bioassay.